Code Switching in the E-Ktp Megacorruption Trial and its Implications for Indonesian Language and Literature Education - Arini Hidayah; Randdie P. Cuelo; Radna Wismawati yahya Sawek (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study analyzes the forms and functions of code-mixing in the language used during the E-KTP megacorruption trial and explores its implications for teaching Indonesian Language and Literature at the senior high school level. Using a qualitative descriptive method, the data were drawn from transcripts of selected trial sessions obtained from CNN Indonesia’s YouTube channel. The dataset is limited to courtroom utterances produced by judges, prosecutors, and witnesses. Methodology: This study uses a qualitative descriptive method. The data consists of transcripts of the E-KTP Megacorruption trial taken from videos on CNN Indonesia's YouTube channel. Data collection techniques were carried out through documentation and observation, while data analysis included reduction, presentation, and drawing and verification of conclusions.. Main Findings: The analysis identifies 21 instances of code-mixing, consisting of 12 words and 9 phrases. Code-mixing primarily functions as a tool of social control, particularly to clarify legal terms and convey perspectives within formal judicial discourse. Most code-mixed forms have equivalent expressions in Indonesian without altering meaning. This study is limited by its focus on a single legal case and a relatively small dataset. Novelty/Originality of this study: The novelty of this research lies in its specific focus on code-mixing in Indonesian courtroom discourse, an area rarely examined in previous studies that mainly address informal contexts. Additionally, the study contributes pedagogically by applying legal discourse findings to the teaching of negotiation texts in secondary education.